Faktor-Faktor yang Berhubungan dengan Keluhan Computer Vision Syndrome (CVS) pada Mahasiswa Teknik Informatika Universitas Muhammadiyah Prof. DR. HAMKA - Gupta, Agi Candra; Mardhiati, Retno; Musniati, Nia (Fakultas Kedokteran Universitas Trisakti, 2023)
Background Computers or laptops are needed for learning and working media for young children of productive age with a university-level education to balance their mobility. However, long-term use of a computer or laptop can cause eye problems, including Computer Vision Syndrome (CVS). This study aims to determine the factors associated with Computer Vision Syndrome (CVS) complaints in Informatics Engineering students at the University of Muhammadiyah Prof. DR. HAMKA South Jakarta in 2022. Methods This research is a quantitative study with a Cross-Sectional study design. The sampling technique uses the Quota Sampling method with 150 respondents. Data collection was carried out using an online questionnaire with google forms. The analysis used is univariate analysis and bivariate analysis. Results The results showed that respondents with positive CVS symptoms (70.7%) with the most complaints were tired and strained eyes (77.3%). The Chi-square test between risk factors and CVS obtained results, gender (p = 0.725), the use of glasses (p = 0.011), duration of exposure to computer or laptop screens (p < 0.0001), taking eyes breaks (p = 0.002), the distance between eyes and computer or laptop screen (p = 0.049), and body position when using a computer or laptop (p = 0.006). Conclusions The significantly related risk factors to CVS were the use of glasses, duration of exposure to computer or laptop screens, taking eye breaks, the distance between eyes and computer or laptop screen, and body position when using a computer or laptop. At the same time, gender is not associated with CVS complaints.